GENDER EQUALITY AND ECONOMIC GROWTH TOWARD FULFILLMENT OF SUSTAINABLE DEVELOPMENT GOALS - Vinsensia P Anggraeni; Nurul Bariyah; Sri Kurniawati (Universitas Negeri Medan, 2022)
In implementing the 2030 Agenda for the Sustainable Development Goals (SDGs), gender equality is fundamental to realizing the promises of sustainability, peace, and human progress. In 2020, females made up 49.42% of Indonesia's total population, while at the same time, Indonesia's score on the Gender Development Index was lower than the world's average GDI score. This study aims to analyze the effect of gender equality on economic growth in Indonesia in 2010-2019. In this study, a descriptive quantitative analysis approach was used, with the research object being the 33 provinces of Indonesia. The model used in this study is a multiple regression equation made to handle panel data. The results showed that Women's Life Expectancy had a negative and significant effect on economic growth. In contrast, Women's Average Length of Schooling has a negative and significant effect on economic growth. The study results revealed that improving the quality of women's human resources as measured by education and health and participation rates is a necessary but not sufficient factor in driving overall economic growth. It needs to be accompanied by proper policies that favor women regarding good job opportunities, a safe work environment, and decent wagesKeywords: Gender, Growth, Life Expectancy, Mean Years of Schooling.